Thoracic surgical interventions for DR-TB and their results. (December 2016) - Dewan, Ravindra Kumar
Abstract: Background: Surgery in DR-TB is a highly contested intervention. However, in suitable selected cases, it has a great role in improving outcomes of treatment as well as symptomatic improvement in the quality of life of the patient. Indications of surgery in this setting will be localized disease with high likelihood of persistent progression or sputum positivity despite adequate therapy. Recurrent hemoptysis, intolerance to drugs or absence of radiological and bacteriological improvement during initial 3–4 months of therapy becomes additional indications for surgical intervention. A review of 11 studies published in a period from 1993 to 2013 provides enough justification for the role of surgical intervention in pulmonary tuberculosis. Interventions: At the NITRD, in the last 20 years a total of 107 cases have been operated upon for DR-TB. Procedures done were 70 pneumonectomies, 20 lobectomies, 5 bilobectomies, 4 nonanatomical resections and 7 thoracoplasties. Results: Sputum negativity was achieved in 93 cases after surgery and 62 were declared cured after 4 years of follow up. 6 cases of DR TB were also operated upon in March 2013 in one MSF TB surgery mission and all of them are sputum negative till March 2015. Conclusions: In conclusion, surgical intervention should be offered and made available for greater number of DR-TB patients.